Inventory Of The Order Orthoptera In Institut Teknologi Sumatera - Maretta, Gres; Sari, Dian Anggria; Darmawan, Andy; Mulyana, Jeane Siswitasari (MAXIMUS: Journal of Biological and Life Sciences, 2025)
Orthoptera is always associated with plant vegetation, as these insects are herbivores and rely on plants as their primary food source. Institut Teknologi Sumatera is home to various types of vegetation and plant diversity, both naturally growing and managed for specific purposes. Based on this background, research is needed to inventory and document the species of grasshoppers found at Institut Teknologi Sumatera and understand their distribution and habitat. Data collection on the diversity of the Orthoptera order was carried out at Institut Teknologi Sumatera and identified in the Zoology Laboratory at Institut Teknologi Sumatera. Sampling was conducted using an insect net and the hand sorting method. Observations were conducted in the morning from 07:00 – 10:00 AM WIB and in the afternoon from 03:00 – 05:00 PM WIB. Based on the research conducted at the Institut Teknologi Sumatera, 12 genera were found at four observation station points. At station I, 161 individuals were found; at station II, 204 individuals were found; at station III, 136 individuals were found; and at station IV, 145 individuals were found. 12 genera of the order Orthoptera were found, belonging to four families. The most commonly found family was Acrididae, while the least commonly found families were Gryllidae and Pyrgomorphidae.